O trabalho colaborativo no cotidiano das práticas pedagógicas escolares: (des)caminhos da formação docente - Góes, Ueslâne Melo de (2019)
Teacher training and pedagogical practices are articulated and constituted as a reflexive and critical daily process, presupposing a dialogical, collective and emancipatory action among students, teachers and other subjects involved in these process. This study aimed to analyze the effects of teacher training and managers of a public school, based on collaborative work. In order to do so, it adopted as a theoretical-methodological assumption the collaborative-critical research-action. It was carried out from March to December of 2017, in a local school of Nossa Senhora do Socorro and involved seven (7) subjects, being five (5) teachers, one (1) coordinator and one (1) director. It was organized in four non-linear moments, configuring the spirals of action-reflection, namely: Moment of constitution of the field; Training groups; closing the training and working with the managers. The data produced were categorized and listed by thematic regularities of analysis and interpreted from the precepts of Lev Vygotsky's Interactionism and the Network of Meanings. This study dialogues with the precepts of Lev Vygotsky's Interactionism and the Network of Meanings. As results, the following stand out: fragile pedagogical practices, almost without reflection and autonomy; homogeneous practices without considering the diversity of the classroom; the sense of collective spaces used; school organization that privileges individual actions, to the detriment of collective actions; incipient relationship between teachers and management; and practices detached from the perspective of inclusive education. From the observation / action in the classrooms can be seen new possibilities in the pedagogical practices and organization of the school routine, in order to suport new teaching practices, and the proximity between teachers and management and use of the collective spaces of the school. It is concluded that collaborative work in the daily school life is potent in the process of professional teacher training and in the process of implementing new pedagogical practices.